2008
DOI: 10.1080/22201173.2008.10872551
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic response to laryngoscopy with and without tracheal intubation

Abstract: IntroductionTracheal intubation is accompanied by an increased blood pressure and heart rate. The aim of this study was to find the most important source of this haemodynamic response, namely laryngoscopy or intubation. MethodA standard induction technique was used for all patients. Eighty patients were randomly allocated to one of two groups, one group to undergo laryngoscopy followed by intubation (Group I), and the other laryngoscopy only of duration similar to intubation (Group L). Blood pressure and heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…The stress response to laryngoscopy and intubation, is a well-known centrally mediated, sympathetic reflex associated with a cardiovascular response, of elevated blood pressure, heart rate and dysrhythmias, cough reflexes, increased ICP and increased intraocular pressure. [ 6 7 8 ] If no specific measures are taken to prevent hemodynamic response, the HR can increase from 26% to 66% depending on the method of induction and SBP can increase from 36% to 45%. [ 9 10 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…The stress response to laryngoscopy and intubation, is a well-known centrally mediated, sympathetic reflex associated with a cardiovascular response, of elevated blood pressure, heart rate and dysrhythmias, cough reflexes, increased ICP and increased intraocular pressure. [ 6 7 8 ] If no specific measures are taken to prevent hemodynamic response, the HR can increase from 26% to 66% depending on the method of induction and SBP can increase from 36% to 45%. [ 9 10 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…15 Smith et al also found that mean arterial pressure and heart rate significantly increased in laryngoscopy with intubation group. 16 Research by Marsaban et al gave results that cardiovascular response and the need of Backwards Upwards Rightwards Pressure (BURP) manuever during laryngoscopy was lower in C-MAC® than conventional laryngoscope (19,3% to 40,3%, p=0,014). 17 Ng et al also stated the similar thing compared to McGrath® laryngoscope, 18 and even lower compared to Macintosh device.…”
Section: Tabel 3 Univariate Analysis For Time Duration Of Intubationmentioning
confidence: 99%
“…Tindakan laringoskopi intubasi biasa dilakukan untuk menjaga jalan nafas, ventilasi mekanik, dan sebagai fasilitasi pemberian gas anestesi, namun dapat menstimulasi refleks batuk, spasme laring, dan sistem saraf simpatis yang berakibat meningkatnya tekanan darah dan denyut nadi yang dapat berbahaya bagi pasien. [1][2][3] Obat-obatan pelumpuh otot dengan dosis yang besar sering digunakan sebagai fasilitasi untuk memudahkan laringoskopi intubasi. 4,5 Tindakan ini diikuti tindakan reversal dengan obat-obat anticholinesterase untuk mendapatkan kembali nafas spontan pasien, yang apabila inadekuat tidak jarang menyebabkan rekurarisasi atau kelumpuhan otot kembali.…”
Section: Pendahuluanunclassified